2009
DOI: 10.1016/j.devcel.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Checkpoint Maintains Cdh1 in an Active State to Inhibit Anaphase Progression

Abstract: DNA damage checkpoint prevents segregation of damaged chromosomes by imposing cell-cycle arrest. In budding yeast, Mec1, Chk1, and Rad53 (homologous to human ATM/ATR, Chk1, and Chk2 kinases, respectively) are among the main effectors of this pathway. The DNA damage checkpoint is thought to inhibit chromosome segregation by preventing separase-mediated cleavage of cohesins. Here, we describe a regulatory network that prevents segregation of damaged chromosomes by restricting spindle elongation and acts in paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 36 publications
4
58
0
Order By: Relevance
“…It has been shown previously that both replication checkpoint and DNA damage checkpoint are capable of restraining spindle elongation. 13,25 However, our study strongly suggests that the task dilution), anti-G6PD polyclonal antibodies (Sigma, 1:10000 dilution), anti-Mad1 antibodies (a gift from Dr Kevin Hardwick) and anti-Rad53 (Santa Curz, 1:1000 dilution), respectively. Enhanced chemiluminescence kit from Santa Cruz was used for all western blot analyses according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been shown previously that both replication checkpoint and DNA damage checkpoint are capable of restraining spindle elongation. 13,25 However, our study strongly suggests that the task dilution), anti-G6PD polyclonal antibodies (Sigma, 1:10000 dilution), anti-Mad1 antibodies (a gift from Dr Kevin Hardwick) and anti-Rad53 (Santa Curz, 1:1000 dilution), respectively. Enhanced chemiluminescence kit from Santa Cruz was used for all western blot analyses according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 95%
“…13 The DNA damage checkpoint has also been reported to regulate mitotic spindle elongation (in parallel with the inhibition of cohesin cleavage) to prevent segregation of damaged chromosomes. 25 Hence, the regulation of spindle dynamics is an important element in the checkpoint control networks in budding yeast. In this study, we have investigated the mechanism underlying the segregation of unreplicated chromosomes in Cdc6-deficient cells.…”
Section: Introductionmentioning
confidence: 99%
“…1a). In contrast, another study recently suggested that there was a Rad53-dependent reduction of Cdc5 activity by *50-66 % in the presence of DNA damage (Zhang et al 2009) and that this lowered Cdc5 activity might prevent normal mitotic progression by maintaining the APC activator Cdh1 (Zhang et al 2009) and the mitotic exit inhibitor Bfa1 in hypophosphorylated states (ValerioSantiago et al 2013) (Fig. 1b).…”
Section: Polo-like Kinasesmentioning
confidence: 91%
“…Many different proteins involved in various cellular processes have been connected to the adaptation response, including cell cycle regulators (Jin and Wang 2006;Toczyski et al 1997;Zhang et al 2009), chromatin-remodeling enzymes (Papamichos-Chronakis et al 2006), autophagy factors (Dotiwala et al 2013), and centrosome/spindle pole body effectors (Hu et al 2001;Valerio-Santiago et al 2013). How this group of apparently disparate proteins regulates the adaptation to DNA damage and whether they work together or in separate pathways to overcome checkpointinduced cell cycle arrest is still unclear.…”
Section: Effectors Of the Adaptation Response To Dna Damagementioning
confidence: 99%
See 1 more Smart Citation